Gagauz People as a Micronation - Hatłas, Jerzy (Poznańskie Studia Slawistyczne, 2015)
This article aims at givng a brief description of the Gagauz people in the areas of Bessarabia and Bulgaria. Gaugazes are a group of elusive people, whose origin seems to be obscure because of only indirect written sources. While in Bulgaria, their old country, Gagauzes maintain Bulgarian identity in addition to their own, in Bessarabia they are a distinct ethnic category. Gaugazes probably can be a micronation, by modern standards. If we consider their culture (spiritual and material), also their history and geography of settlement, they can be categorized as a Slavonic micronation. Nevertheless, their language and origins seem to be non-Slavic.